The woman who knew too much : Alice Stewart and the secrets of radiation - Greene, Gayle, 1943- (Ann Arbor [Michigan] : University of Michigan Press, 2017)
The Woman Who Knew Too Much illuminates the life and achievements of the remarkable woman scientist who revolutionized the concept of radiation risk. For more than 40 years, Alice Stewart (1906-2002) warned that low-dose radiation was more dangerous than anyone acknowledged. In the 1950s she discovered that fetal x-rays double a child's risk of developing cancer. Two decades later, in her 70s, she again astounded the scientific world by showing that the U.S. nuclear weapons industry was about 20 times more dangerous than safety regulations admitted. This finding put her at the center of an international controversy over radiation risk. In 1990, the New York Times called Stewart "perhaps the Energy Department's most influential and feared scientific critic." Author Gayle Greene traces Stewart's life and career as she came up against ever more powerful authorities, first the British medical profession, then the U.S. nuclear industry, and finally the regulatory agencies that set radiation safety standards throughout the world. Stewart endured the fate of other women scientists in having her findings dismissed and funding cut, but today is recognized as a pioneering figure in epidemiological research on the dangers of nuclear radiation. In her preface to the second edition, Greene looks at new information that's come out about the forces and individuals responsible for marginalizing her as a scientist and downplaying the disturbing implications of her research.
Preface to the second edition -- 1. Introduction : daughter of time -- part 1. The making of a doctor -- 2. Dr. Lucy and Daddy Naish -- 3. School days and Cambridge -- 4. Marriage, motherhood, medical practice : through the war years -- part 2. Engendering epidemiology -- 5. Changing subjects -- 6. X-rays and childhood cancer -- 7. Dr. Doolittle's team for the moon -- part 3. Through the looking glass, onto the international nuclear scene ... -- 8. Up against the Department of Energy -- 9. Taking on the international nuclear regulatory system -- 10. Rogue scientists -- 11. Alice in Blunderland : back in Britain -- 12. Fallout -- 13. The invisibilizing of Alice -- part 4. A message to the planet -- 14. Epidemiology and Alice Stewart -- 15. The good doctor -- 16. Pioneer and pariah -- 17. Endings.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Stewart, Alice M. -- 1906-2002 -- Political activity; Stewart, Alice M. -- 1906-2002.; Stewart, Alice M. -- 1906-2002; Stewart, Alice M. -- 1906-2002; Radiation -- Health aspects; Radiation injuries -- Prevention -- Political aspects; Women physicians -- England -- Biography; Femmes médecins -- Angleterre -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Medical; HEALTH & FITNESS -- Holism; HEALTH & FITNESS -- Reference; MEDICAL -- Alternative Medicine; MEDICAL -- Atlases; MEDICAL -- Essays; MEDICAL -- Family & General Practice; MEDICAL -- Holistic Medicine; MEDICAL -- Osteopathy; Political participation; Radiation -- Health aspects; Women physicians; England; Radiologie; Biographies